EVALUASI KOMPLIKASI PLATE EXPOSURE PASCA RESEKSI AMELOBL ASTOMA MANDIBULA DENGAN REKONSTRUKSI PELAT TITANIUM DI RSUP DR. SARDJITO YOGYAKARTA - Maria Goreti Widiastuti; Marsetyawan HNE Soesatyo; Rahardyan Magetsari; Alva Edy Tontowi (Jurnal Teknosains, 2016)
Resection of the jaw is a primary option of treatment in mandibular ameloblastoma with bone damage. Mandibular resection will cause mandibular stability disturbance due toloss of some part of the bone. Instability of the mandible can cause aesthetic, physiological, and psychological malfunctioning. To restore its stability, installment of mandibular reconstruction plate on the remaining mandibular by using screws. However, it is not uncommon that plate exposure occurs following mandibular reconstruction, caused by inaccurate adaptation of the plates to the mandibular bone. A  3D stereolithography modelcan help provide the best assesment on the bone defect, plan the making of the more easily pre-operative curved plates and provide more accurate faster surgery time. Objective: To evaluate plate exposure after mandibular resection with titanium reconstruction plates in Dr. SardjitoHospital. Case report: A case was reported on mandibular reconstruction after resection of ameloblastoma with titanium plate performed in Dr. Sardjito Hospital that experienced intra-oral plate exposure and oro-cutaneous fistula on the left mandible. The clinical evaluation showed the curved titanium plate did not adapt well with the remaining mandibular bone; therefore, the titanium plate was removed without replacing it with a new plate. Inappropriate adaptationof curved titanium plate is one of the main causes of plate exposure. The use of a 3D stereolithography model is very helpful for the success of mandibular reconstruction.